PERANCANGAN APLIKASI GAME EDUKASI TENTANG MITOLOGI INDONESIA BERBASIS ANDROID - Alvin, Alvin; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2023)
The rapid development of technology has significantly impacted various aspects of human life, including education and entertainment. One emerging trend is the utilization of technology to create engaging and interactive educational games. With technological advancements, educational games have become effective tools to teach various concepts and skills to the younger generation. However, in the era of globalization, the role of mythology in the lives of the younger generation has been overshadowed by foreign cultures' influence and technological advancements. By combining technology, elements of mythology, and educational aspects, a game based on Indonesian mythology becomes an innovative and attractive solution to ignite the interest and awareness of the younger generation towards their cultural heritage and national history. In this research will developed a technology-based educational game with a focus on Indonesian mythology using Unity, Adobe Illustrator and Visual Studio. The game was designed to present information about Indonesian mythology in an engaging and interactive manner, captivating the interest of the younger generation in learning and getting acquainted with their cultural heritage.